HONEY PUMPKIN STEM BORER, Apomecyna saltator FABRICIUS (COLEOPTERA: CERAMBYCIDAE) CAN BE CONTROLLED WITH PHOSPHORUS AND POTASSIUM FERTILIZER - Wilyus, Wilyus; Nurdiansyah, Fuad; Irianto, Irianto; Asniwita, Asniwita; Oktavia, Sella (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Apomecyna saltator, a notorious pest of honey pumpkin plants, poses a significant threat to both vegetative and generative phases, leading to considerable production losses. Despite its agricultural impact, there are limited studies on effective management strategies for this pest. This research investigates the effect of combined phosphorus and potassium fertilization on controlling A. saltator infestations in honey pumpkin plants. The study was conducted at the Teaching and Research Farm of the Faculty of Agriculture, Jambi University. A randomized block design with five treatments and five replications was used, testing different combinations of SP-36 phosphorus and potassium chloride (KCl) fertilizers: no fertilization (p0), SP-36 0.67 g/plant + KCl 1.25 g/plant (p1), SP-36 1.00 g/plant + KCl 1.88 g/plant (p2), SP-36 1.34 g/plant + KCl 2.51 g/plant (p3), and SP-36 1.67 g/plant + KCl 3.13 g/plant (p4). The variables observed included stem diameter, larval population, percentage of plant damage, number of attacked plant segments, fruit weight, and overall production. Data were analyzed using ANOVA and Duncan's Multiple Range Test (DMRT). The results indicated that combining phosphorus and potassium fertilizers significantly increased stem diameter, fruit weight, and yield while reducing larval populations, plant damage, and affected segments. The study demonstrates that phosphorus and potassium strengthen honey pumpkin plants and negatively impact A. saltator infestations. This research highlights a novel approach to pest control, showing that targeted fertilization promotes plant health and suppresses the honey pumpkin stem borer (A. saltator). This dual benefit of nutrient application provides a sustainable and efficient pest management strategy, offering a fresh perspective on integrated crop protection.